Design, synthesis, and biological evaluation of target water‐soluble hydroxamic acid‐based HDACi derivatives as prodrugs. (19th June 2019) - Li, Jun; Zhu, Yedan; Xie, Miaohong; Zhang, Qian; Du, Wenting
Abstract: Four compounds T1, T2, T3, and T4 were designed and synthesized as Vorinostat and Belinostat derivatives being the target water‐soluble prodrugs. The water solubility of Vorinostat derivatives, T1 and T2, exhibited 400‐ to 600‐fold higher than that of Vorinostat, and Belinostat derivatives, T3 and T4, showed 600‐ to 750‐fold higher than that of Belinostat. Four compounds were evaluated for their inhibitory activities against tumor cell lines HT‐29 and Hut‐78 in the absence or presence of β‐D‐glucuronidase. The inhibitory effects of T1 and T2 were comparable to Vorinostat in the presence of β‐D‐glucuronidase, but were higher than 10 μM in the absence of β‐D‐glucuronidase. Therefore, T1 and T2 are promising candidates for in vivo investigations with high potential to be the target water‐soluble prodrugs. IC50 values of Belinostat derivatives T3 and T4 were not affected by β‐D‐glucuronidase, but T3 and T4 had the excellent cell proliferation inhibition on Hut‐78. Abstract : Four compounds T1, T2, T3, and T4 were designed and synthesized as target water‐soluble Vorinostat and Belinostat derivatives as prodrugs, and then evaluated against tumor cell lines HT‐29 and Hut‐78 in the absence or in the presence of β‐D‐glucuronidase. T1 and T2 demonstrated high potential to become the target water‐soluble prodrugs.